Mosaicism for copy number variations in the placenta is even more difficult to interpret than mosaicism for whole chromosome aneuploidy. (24th April 2021) - Lund, Ida C. Bay; Becher, Naja; Graakjaer, Jesper; Lildballe, Dorte L.; Uldbjerg, Niels; Bogaard, Pauline; Petersen, Astrid; Vestergaard, Else M.; Vogel, Ida
Abstract: Objective: To compare mosaicisms in prenatal chorionic villus samples (CVSs) with corresponding postpartum placental samples. Method: We collected placentas from 15 consecutive cases of mosaicism detected in CVSs and obtained five standardized samples on each placenta after delivery. All pre‐ and postnatal placental samples were uncultured and analyzed by high‐resolution chromosomal microarray. Results: Ten cases of mosaicism for whole chromosome aneuploidy (mWC) and five cases with mosaicism for (sub)chromosomal copy number variations (mCNVs) were included. In 5/10 mWC cases and in 4/5 mCNV cases the prenatally detected aberration was confirmed in the postpartum placenta. Three postpartum placentas revealed various complex aberrations differing from the prenatal results: (1) mosaicisms for different deletions/duplications on 9p and 9q in all samples (prenatal: mosaic 5.3 Mb duplication on 9p24), (2) different regions with deletions/duplications/loss of heterozygosity on 1p in all samples (prenatal: mosaic 2.3 Mb 1p36 duplication), and (3) mosaicism for a duplication on 5q and a deletion on 6p in one out of five samples (prenatal: mosaic trisomy 7). Conclusion: CNVs constitute a complex subgroup in placental mosaicism. Counseling of these couples after chorionic villus sampling should not focus on the specific CNV involved, but on the nature of mosaicism and the option of amniocentesis and ultrasound. Key points: What's already known about this topic? Mosaicism for copy number variations (CNVs) of any size detected in chorionic villus samples (CVSs) may involve the fetus. CNVs detected by amniocentesis may be discordant to aberrations detected in the postpartum placenta. What does this study adds? CVS mosaicism for CNVs may be unreliable in predicting fetal CNVs as such findings may differ from CNVs in the postpartum placenta. Counseling should not focus on the CNV region involved but on the option of amniocentesis.